Strategi Pengelolaan Konten Tiktok Lembaga Sensor Film RI dalam Meraih Engagement Rate - Amalia Rizky Indah Permadani; Nurudin Nurudin (Unitri Press, 2023)
The Indonesian Film Censorship Institute (LSF) is a government agency that operates in the field of film censorship. This institution has the authority to censor films, film advertisements, examine themes, scenes, text, sound and images before they are released, shown or shown to the public. LSF also has the task of conducting outreach to the public through social media, one of which is Tiktok LSF RI which aims to convey information, education and the Independent Censorship Culture campaign. Tiktok LSF RI is operated by the Chair of the LSF New Media Sub-Commission. The aim of this research is to determine content management strategies to achieve engagement levels and so that messages can be conveyed to the audience. This study used descriptive qualitative method. Data collection was carried out through observation, documentation and interviews. The research was conducted for 2 months at LSF RI Jakarta. As a result of this research, the Publication Team succeeded in increasing the engagement rate by 3.13% in a period of three months, the content was more thematic, conceptual, relatable, entertaining, the selection of talent had good visuals and matched the content idea, and had video quality with the best resolution. Their strategy in managing LSF social media content is through planning, activation and monitoring and optimization. Abstrak Lembaga Sensor Film (LSF) RI merupakan instansi pemerintah yang bergerak di bidang penyensoran film. Lembaga ini berwenang untuk melakukan sensor film, iklan film, memeriksa tema, adegan, teks, suara dan gambar sebelum diedarkan, dipertunjukkan maupun ditayangkan kepada khalayak. LSF juga punya tugas untuk melakukan sosialisasi ke masyarakat melalui media sosial, salah satunya adalah Tiktok LSF RI yang bertujuan untuk menyampaikan informasi, edukasi dan kampanye Budaya Sensor Mandiri. Tiktok LSF RI dioperasikan oleh Ketua Sub Komisi Media Baru LSF. Tujuan dari penelitian ini adalah untuk mengetahui strategi pengelolaan konten untuk meraih engagement rate serta agar pesan dapat tersampaikan ke audiens. Penelitian ini menggunakan metode kualitatif deskriptif. Pengumpulan data dilakukan melalui observasi, dokumentasi dan wawancara. Penelitian dilakukan selama 2 bulan di LSF RI Jakarta. Hasil dari penelitian ini, Tim Publikasi berhasil meningkatkan engagement rate sebesar 3,13% dalam kurun waktu tiga bulan, konten lebih tematik, terkonsep, relatable, menghibur, pemilihan talent bervisual bagus dan cocok dengan ide konten, serta memiliki kualitas video dengan resolusi terbaik. Strategi mereka dalam mengelola konten media sosial LSF yaitu melalui perencanaan, aktivasi dan pengawasan dan optimalisasi.